Wild Italian Hyssopus officinalis subsp. aristatus (Godr.) Nyman: From Morphological and Phytochemical Evidences to Biological Activities - Alessandra Guerrini; Gianni Sacchetti; Monica Paulina Echeverria Guevara; Guglielmo Paganetto; Alessandro Grandini; Immacolata Maresca; Luigi Menghini; Luciano Di Martino; Arianna Marengo; Massimo Tacchini (Plants, 2021)
Three specimens of H. officinalis subsp. aristatus were collected in three areas of the Abruzzo region (Italy) and subjected to macroscopic and microscopic observation to support their botanical identification. The essential oils (EOs) obtained from the aerial parts of the samples were characterized with the object to define their phytochemical and pharmaceutical biology profile. They highlight three different chemotypes, including one never seen in previous literature (CIV17-EO, distilled from sample harvested in 2017 at Civitaretenga), that showed a fingerprinting with the predominance of (-)-limonen-10-yl-acetate (67.9%). In 2017 European Food Safety Authority (EFSA) reported the genotoxicity of similar compounds, therefore, to dismiss any safety concern for the CIV17-EO use as flavouring substance, the Ames test was performed with no evidence of mutagenic activity. Safety of use coupled with chemical characterization of this new chemotype set the stage for a better standardization of H. officinalis EOs. The ethanolic extracts, on the other hand, with qualitatively similar chemical profiles in which caftaric, chlorogenic and rosmarinic acid were the main molecules, showed interesting antioxidant activity and a slight cytotoxicity towards the A549 cell line that could indicate a starting point for the evaluation of an additional preventive tool for maintaining health status.